(untitled) (ArtCultura, 2011)
Aristóteles afirmou serem três os gêneros retóricos (judiciário, deliberatico e epidítico), distinguindo-os pelas circunstâncias, auditórios e tempo em que se fala. Tal divisão, ainda que com nuanças, mantém-se em Quintiliano. Os tratados eclesiásticos de retórica também a seguem, embora mudanças significativas aqui sejam efetuadas, tendo em vista o efeito persuasório próprio da prédica religiosa. Utilizando-se de tal prescritiva, sobretudo conforme a apresenta frei Granada, o padre Antônio Vieira no Sermão da Sexagésima exemplarmente apresenta um modelo para os gêneros que, via de regra, decorosamente se adéqua à finalidade do que ele próprio prescreve como paradigma para qualquer sermão. PALAVRAS-CHAVE: gêneros retóricos; retórica eclesiástica; Sermão da Sexagésima. ABSTRACT: In 1979, ï¬lm-maker Leon Hirszman (1937-1987) collaborated with playwright Gianfrancesco Guarnieri on a ï¬lm adaption of Guarnieri’s famous play about Brazilian working-class life, They don’t wear black-tie. The resulting ï¬lm, released in 1981, reconï¬gured the politics and content of the 1958 play to ï¬t the new era of the late 1970s when dramatic metalworkers’ strikes placed São Paulo on the front lines in the ï¬ght against the Brazilian military dictatorship. Using biography and the dramatic and cinematic texts, this article traces the political and aesthetic challenges facing these two important cultural ï¬gures and their generation of radical intellectuals. In particular, the article will explain why an image of "workers" proved so central in the making of modern Brazilian theater and ï¬lm since the late 1950s, while exploring the changing conï¬guration of intellectual and povo (common people) between the late Populist Republic and the remaking of the Brazilian working class during the late 1970s. Throughout, it will ask: What is the cultural, political, and historical substance or signiï¬cance of the presentation of workers in Black-tie? Does it represent an expression of social reality? And if so, what reality, and whose vision?